A Pendulum of Innovations and Challenges: Technological System and Industrial Heritage of Sulphur Mining in Northern Chile (1887–1993). (2nd January 2020) - Rivera, Francisco
ABSTRACT: Located at the Bolivian border in the Antofagasta region, Ollagüe saw the emergence of industrialisation and capitalist expansion through sulphur mining activities during the 20th century. This article presents both an historical synthesis and the industrial heritage of Ollagüe to show how the innovations in the sulphur mining technological system go hand in hand with the global economic context of the last century. Archaeological industrial heritage is approached here in terms of continuity and ruptures; in other words, as a constant pendulum movement of technological innovations and production challenges.